PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA KONSUMEN KOPI KENANGAN DI RUKO NGAGEL, SURABAYA - Letisia Letisia; Dyah Rini Prihastuty (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The purpose of this study is to prove and analyze the impact of service quality, price perception, and customer satisfaction on customer loyalty among Kopi Kenangan consumers at Ruko Ngagel, Surabaya. This research uses a quantitative method with a sampling technique involving 100 respondents who are customers of Patas Jastip. The data obtained were processed using SPSS version 26.0, and the tests used in this study include Instrument Testing (Validity and Reliability Tests), Classical Assumption Testing (Normality, Multicollinearity, and Heteroscedasticity Tests), Multiple Linear Regression Analysis, and the Coefficient of Determination Test, while hypothesis testing is conducted using the F and T tests. The results of the study indicate that service quality, price perception, and customer satisfaction significantly affect customer loyalty among Kopi Kenangan consumers at Ruko Ngagel, Surabaya. Simultaneously, the variables of service quality, trust, and customer satisfaction influence customer loyalty among Kopi Kenangan consumers at Ruko Ngagel, Surabaya.